Pengembangan Masyarakat Islam Melalui Penanaman Nilai-Nilai Tasawuf Di Lingkungan Pedesaan - hilmi, fuad (Medpro, 2022)
The development of Islamic society through the cultivation of applied Sufism values ​​combines religious studies and social theory to build society. The aim is to overcome social problems, explore potential, empower society, and encourage social change towards the desired society, by applying religious values ​​in everyday life. This research aims to review the role of cultivating Sufism values ​​in developing Islamic society in Kudadepa Village, Sukaheuning District, Tasikmalaya Regency. The research method used was descriptive qualitative with purposive sampling of subjects. Data was collected through observation, interviews and documentation with research subjects including village officials, community leaders and village residents. Data analysis is carried out through the stages of data collection, data reduction, data display and verification. The results of the research show that the development of an Islamic society through instilling Sufism values ​​in Kudadepa Village is reflected in improvements in the economy, social, politics, culture, education and especially in the religious sector. This success was verified through observation, interviews and documentation. In conclusion, the development of Islamic society through instilling Sufism values ​​is very effective in improving the welfare of Islamic society.